TRANSFORMATION OF VALUES IN THE 21ST CENTURY - Atadjanov Mamirjon Yusupovich (Bright Mind Publishing, 2025)
This article highlights the process of transformation of values in the modern world, in particular, changes in consumer culture and their impact on ethics and gender issues.
Keywords: Values, consumer culture, advertising influence, fraud, behavioral disorders.